Testing of Technical Indicators of Accumulators by Means of Complex Computer Model of EV - Fedotovs, Jurijs; Bunina, Inna; Zhiravetska, Anastasia; Andrianova, Svetlava (Electrical, Control and Communication Engineering, 2020)
The accumulators utilized in electric transport differ from those of other applications. Their main features are high capacity, minimum size and weight, and reasonable price. There is extensive research worldwide to improve the battery technology. The aim of the research is to create a mathematical model of an electric vehicle that can capture the vehicle speed curve as a data input to generate the consumed and recovered battery current, which can allow the battery parameters to be analysed and conclude whether the vehicle can perform the trip around the city route with the selected battery parameters. This model serves as a tool to simplify and speed up the necessary calculations and to examine individual sections of the route and their impact on the battery. To complete this task, a simplified electric transport mathematical model gives an opportunity to check if the selected battery can be used in the electrical public transport of the city. The input parameters of the model are the parameters of electrical transport. Simulation of the most popular types of batteries has been performed for two routes of buses in Jelgava in order to determine whether the chosen batteries can provide the necessary bus movement. The mathematical model has been developed in the MATLAB/Simulink software. A GPS mobile application SpeedTracker has been used for data logging.